Irrational Equations and Specific Features of Determining their Solution (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This in the article irrational equations and them solve methods about wide comprehensive concepts given Irrational equations roots, logarithms or another irrational functions own into received are equations. In the article irrational of Eqs types, them of solving main methods and different examples with in detail analysis done This article mathematician knowledge deepening and irrational equations with to work facilitate for useful that we count.